Advantages and Problems of nurses in care of infant feeding in primary care - Águida Porfírio Moura, Mayara; Santiago da Rocha, Silvana; Moura Pinho, Diana Lúcia; Guilhem, Dirce (O Mundo da Saúde, 2015)
In Brazil, the expansion of the primary care network in recent years and the changes in children’s nutritional status reflected in new advantages and difficulties in children’s nursing care. The aim of the study was to report the strengths and difficulties in nursing care related to infant feeding in the nursing in the routine day in primary care network of Teresina-PI. As regards methodology, we opted for a qualitative study, based on thematic oral history. We interviewed 16 nurses of effective primary care network using a semi-structured interview. The interviews were recorded and transcribed, continuing analysis of oral history. In the results and discussion, it was identified that the advantages in nursing care on infant feeding involve the fol- lowing categories: 1) Child and Family; 2) Nurse; and 3) Primary Care Unit. As for the difficulties, these focus on children’s universe, encompassing social, cultural and economic factors of context. We conclude that the reported strengths can be constituted in a lever for nursing care and the difficulties pose obstacles to be overcome by nurses and are explored in other studies. It is evident to the study the importance of nutrition and nursing care for the promotion of children’s health and their quality of life.